Cultivating Bus Rapid Transit (BRT) Station Areas within Freight Rail Corridors: Perceptions and Reality - Baker, Dwayne Marshall; Linovski, Orly (Canadian Planning and Policy / Aménagement et politique au Canada, 2025)
Using rail corridors for BRT may limit right-of-way costs, yet little is known about the land development impacts of this model. This research examines the perceptions and outcomes of implementing BRT station area developments within freight rail corridors using (1) surveys with planners, homebuilders, and developers and (2) Poisson regressions of building permit data in Winnipeg, Canada. Our survey results show that while planners do not view the existence of freight lines positively, homebuilders and developers do not see rail corridors as a barrier to development. This is confirmed by regression results of permit data that show that Winnipeg has experienced more non-detached single-family dwellings, like row- or townhouses, in close proximity to BRT stations. These findings demonstrate that while planners perceive rail lines as a barrier to transit-oriented development, in some cases, land adjacent to rail lines exhibit significant development interest from a market perspective.